Do the outstanding comments of regulatory reviewers for approved IPOs serve as a valuation signal for investors? - Xuxia Chen; Jun Wang; Xi Wu (China Journal of Accounting Studies (CJAS), 2022)
Since 2015, the China Securities Regulatory Commission (CSRC) has disclosed initial public offering (IPO) companies' review outcomes and hearing questions. For 15% of the companies that pass the IPO screening process, the CSRC also discloses some of their hearing questions that require further disclosure and clarification after the IPO screening process (termed outstanding comments herein). A company passing the vote means that it has received general approval from the majority of review experts. However, outstanding comments also reflect that some review experts have remaining concerns about the IPO applicant. Results show that approved IPO companies with outstanding comments perform significantly worse than those without outstanding comments both before and after listing, suggesting that outstanding comments serve as a signal of a stock's valuation. Moreover, investors (particularly institutional ones) appear to perceive the signal of outstanding comments, as they react more negatively around the listing date of such companies.
Keywords: 650; IPO screening process; hearing questions; outstanding comments; valuation signal; investor reaction